ALFRED ADLER’S INDIVIDUAL PSYCHOLOGY IN PROTAGONIST OF “SOUL” MOVIE (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to describe the individual psychological aspects of the protagonist, Joe, in the movie Soul, and to describe the principle that dominately influences the protagonist's personality. This study uses a qualitative descriptive method with data analysis techniques and literary psychology approach. The theory used is Alfred Adler's individual psychology theory. The data source for this study is the film Soul directed by Pete Docter. The results of this study indicate that Joe's character contains the six principles of Alfred Adler's individual psychology, and there are some of them that dominate his personality.